Breaking the Silence Poetry and the Kenotic Word - Grzegorzewska, Małgorzata 1964- (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2015)
This book of essays on poetic speech, viewed in a literary-critical, theological and philosophical light, explores the connections and disconnections between vulnerable human words, so often burdened with doubt and pain, and the ultimate kenosis of the divine Word on the Cross. An introductory discussion of language and prayer is followed by reflections linking poetry with religious experience and theology, especially apophatic, and questioning the ability of language to reach out beyond itself. The central section foregrounds the motif of the suffering flesh, while the final section, including essays on seventeenth-century English metaphysical poetry and several of the great poets of the twentieth century, is devoted to the sounds and rhythms which give a poem its own kind of «body».
Description based on publisher supplied metadata and other sources
Keywords: Philosophie; Incarnation -- Philosophy; Incarnation in literature; Silence in literature; Religion; Lyrik; Kenosis; Englisch; Aufsatzsammlung